Importance of Windows of Exposure to Maternal High-Fat Diet and Feto-Placental Effects: Discrimination Between Pre-conception and Gestational Periods in a Rabbit Model - Rousseau-Ralliard, Delphine; Aubrière, Marie-Christine; Daniel, Nathalie; Dahirel, Michèle; Morin, Gwendoline; Prézelin, Audrey; Bertrand, Jérémy; Rey, Catherine; Chavatte-Palmer, Pascale; Couturier-Tarrade, Anne (Frontiers in Physiology, 2021)
Context and Aim: Lipid overnutrition in female rabbits, from prepuberty, leads to impaired metabolism (dyslipidemia and increased adiposity) and follicular atresia, and, when continued during gestation, affects offspring phenotype with intrauterine growth retardation (IUGR) and leads to placental and lipid metabolism abnormalities. Growth retardation is already observed in embryo stage, indicating a possible implication of periconceptional exposure. The objective of this study was to discriminate the effects of preconception and gestational exposures on feto-placental development. Materials and Methods: Rabbit 1-day zygotes were collected from female donors under control (CD) or high-fat-high-cholesterol (HD) diet and surgically transferred to the left and right uterus, respectively, of each H (n = 6) or C (n = 7) synchronized recipients. Close to term, four combinations, CC (n = 10), CH (n = 13), HC (n = 13), and HH (n = 6), of feto-placental units were collected, for biometry analyses. Fatty acid (FA) profiles were determined in placental labyrinth, decidua, fetal plasma, and fetal liver by gas chromatography and explored further by principal component analysis (PCA). Candidate gene expression was also analyzed by RT-qPCR in the placenta and fetal liver. Data were analyzed by Kruskal–Wallis followed by Dunn’s pairwise comparison test. Combinations of different data sets were combined and explored by multifactorial analysis (MFA). Results: Compared to controls, HH fetuses were hypotrophic with reduced placental efficiency and altered organogenesis, CH presented heavier placenta but less efficient, whereas HC presented a normal biometry. However, the MFA resulted in a good separation of the four groups, discriminating the effects of each period of exposure. HD during gestation led to reduced gene expression (nutrient transport and metabolism) and big changes in FA profiles in both tissues with increased membrane linoleic acid, lipid storage, and polyunsaturated-to-saturated FA ratios. Pre-conception exposure had a major effect on fetal biometry and organogenesis in HH, with specific changes in FA profiles (increased MUFAs and decreased LCPUFAs). Conclusion: Embryo origin left traces in end-gestation feto-placental unit; however, maternal diet during gestation played a major role, either negative (HD) or positive (control). Thus, an H embryo developed favorably when transferred to a C recipient (HC) with normal biometry at term, despite disturbed and altered FA profiles.